Psychological symptoms, quality of life and dyadic relations in family members of intensive care survivors: a multicentre, prospective longitudinal cohort study - Sumeet Rai; Dale M. Needham; Rhonda Brown; Teresa Neeman; Krishnaswamy Sundararajan; Arvind Rajamani; Rakshit Panwar; Mary Nourse; Frank M. P. van Haren; Imogen Mitchell; for the PRICE study investigators (Annals of Intensive Care)
Abstract Background There is scarce literature evaluating long term psychological or Quality of Life (QoL) outcomes in family members of ICU survivors, who have not experienced invasive ventilation. The objective was to compare long-term psychological symptoms and QoL outcomes in family members of intubated versus non-intubated ICU survivors and to evaluate dyadic relationships between paired family members and survivors. Methods Prospective, multicentre cohort study among four medical-surgical ICUs in Australia. Adult family members of ICU survivors and family-survivor dyads had follow-up assessments (3 and 12 months after ICU discharge), using Impact of Event Scale-Revised; Depression, Anxiety Stress Scales-21; EQ-5D-5L. Dyadic relationships examined associations of psychological symptoms or QoL impairments. Results Of 144 family members (75% female, 54% partners/spouses) recruited, 59% cared for previously intubated survivors. Overall, 83% (110/132) of eligible family members completed ≥ 1 follow-up. In family members of intubated vs non-intubated survivors, clinically significant psychological symptoms (PTSD/depression/anxiety) were reported by 48% vs 33% at 3-months (p = 0.15); and 39% vs 25% at 12-months (p = 0.23). Family self-rated their QoL with a mean score of 83 (SD 13) on a visual analogue scale (range 0–100), and > 30% reported problems in pain/discomfort or anxiety/depression domains at 12-months. Family members were more likely to have persistent psychological symptoms of PTSD [OR 4.9, 95% CI (1.47–16.1), p = 0.01] or depression [OR 14.6, 95% CI (2.9–72.6), p = 0.001]; or QoL domain problems with pain/discomfort [OR 6.5, 95% CI (1.14–36.8), p = 0.03] or anxiety/depression [OR 3.5, 95% CI (1.02–12.1), p = 0.04], when the paired survivor also reported the same symptoms. Conclusions Almost one-third of the family members of ICU survivors reported persistent psychological symptoms and QoL problems at 12-months. There was a noticeable dyad effect with family members more likely to have persistent symptoms of PTSD, depression, and problems in QoL domains when the paired ICU survivors experienced similar symptoms. The family members of non-intubated ICU survivors had an equal propensity to develop long-term psychological distress and should be included in long-term outcome studies. Future recovery intervention trials should be aimed at ICU family-survivor dyads. Trial registration ACTRN12615000880549